Pengaruh Penerapan Akuntansi Pertanggungjawaban, Kompetensi dan Komitmen Organisasi Terhadap Kinerja Manajerial - Cahyani, Kadek Novita; Damayanthi, I Gst Ayu Eka (E-Jurnal Akuntansi, 2019)
Managerial performance is very important for a company because it can be used to measure the success of the company. A manager needs to implement a managerial control system that can be used to achieve the company goals. The purpose of this study is to obtain empirical evidence regarding the effect of applying accountability accounting, competence and organizational commitment to the managerial performance of the financial division on PT Pegadaian Kota Denpasar. Sampling technique that used in this study is non probability sampling with purposive sampling method. The amount of sample in this study are 52 samples. The analysis technique is multiple linear regression. Based on the results of the analysis shows that accountability accounting, competence, and organizational commitment have a positive effect on the managerial performance of financial division on PT. Pegadaian Kota Denpasar. Keywords : Accountability accounting, competence, organizational commitment, managerial performance.